Disconnect Between Hadley Cell and Subtropical Jet Variability and Response to Increased CO2. Issue 12 (26th June 2019) - Menzel, Molly E.; Waugh, Darryn; Grise, Kevin
Abstract: The subtropical jet (STJ) is thought to coexist with the edge of the Hadley cell (HC). However, recent studies reveal that the location of the STJ is poorly correlated with the latitude of the poleward edge of the HC. Here we use output from the Coupled Model Intercomparison Project Phase 5 to show that a weaker STJ is associated with a more poleward HC edge interannually, but there is a strengthening of the STJ and expansion of the HC in response to increased CO2 . The HC expansion caused by increased CO2 is much more rapid than the strengthening of the STJ. It is suggested that the differing response times and relationships between interannual variations and increased CO2 are due to differing sensitivities of the HC and STJ to shifts in the eddy momentum fluxes. Key Points: CMIP5 analysis shows the STJ latitude does not covary interannually with the HC edge but the STJ strength does moderately The interannual relationship between HC edge and STJ strength is the opposite sign as the response to increased atmospheric CO2 The differences in the HC‐STJ relationship are related to the differing sensitivities of the HC and STJ to shifts in eddy momentum fluxes